International organizations in promoting academic integrity in a globalized world: Ukrainian view - Artem Artyukhov; Dmytro Chumachenko (Geopolitics under Globalization)
Type of the article: Reflexive Preface AbstractThis study aims to examine the role of international organizations in promoting academic integrity, analyzing how diverse cultural interpretations of scholarly ethics create challenges for standard consistency across borders and the mechanisms through which international bodies facilitate the coordination and standardization of integrity practices. A comparative approach examines academic integrity across different jurisdictions and cultural contexts, a multi-level analytical framework understands the organizational structure of academic integrity governance, and illustrative case studies demonstrate practical applications. The analysis identifies five interconnected components of academic integrity: educational, research, managerial, professional association, and publishing integrity. This study reveals a sophisticated five-level hierarchical system of academic integrity governance spanning from international organizations to individual practitioners. International organizations function as collaborative facilitators rather than rigid rule-makers, developing flexible frameworks that can be adapted to diverse cultural contexts while maintaining universal ethical principles. Significant variations exist between national approaches, with some countries implementing comprehensive legislative frameworks while others relying on cultural principles and institutional traditions. International organizations facilitate dialogue and consensus-building that transcends national boundaries while respecting institutional autonomy. The hierarchical governance system demonstrates that academic integrity assurance requires top-down coordination to establish consistent standards and bottom-up commitment to implement those standards. The strength of this system lies in its ability to maintain the universality of core ethical principles while allowing for cultural adaptation in implementation methods, ultimately ensuring that the fundamental commitment to honesty, originality, and fairness in scholarship remains constant regardless of cultural context or geographical location. Acknowledgment The research is prepared in the frame of the project “OSEE – Open Science and Education in Europe: success stories for Ukrainian academia” (project number ERASMUS-JMO-2022-HEI-TCH-RSCH-101085198). Funded by the European Union. The views and opinions expressed are, however, those of the authors only and do not necessarily reflect those of the European Union or EACEA. Neither the European Union nor the granting authority can be held responsible for them.